Gambaran Drug Related Problems (DRPs) pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Tuminting - Tampa'i, Randy; Sumombo, Jacklyne; Hariyadi, Hariyadi; Lengkey, Yessie (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Diabetes mellitus (DM) is a chronic disease with a very high complication rate and the third-highest cause of death in Indonesia. The management of DM cannot be separated from the action of drug therapy. It is necessary to have pharmaceutical care in handling drug related problems (DRPs) in order to achieve optimal drug effects on patients. The purpose of this study is to describe the characteristics and incidence of DRPs in type 2 DM patients at the Tuminting Public Health Centre, Manado. Sampling of 42 samples is conducted with a purposive sampling method using medical records and patient medical treatment history data for type 2 DM patients retrospectively from January to June 2019. The data is analyzed descriptively. The results obtained from the incidence of type 2 diabetes mellitus in women were 53.10% and men 46.90%. Most patients with type 2 diabetes were at the age of >60 years, 66.67%. The highest co-morbidity were cardiovascular disorders 24,24%. The most widely used antihyperglycemic drug was metformin 72.50%. The most DRPs incidence occurred in May 2019 at 36.36%, with 59.05% was needing drugs was, 13.64% did not need drugs, 20.45% wrong drugs, 2.27% less dose and 4.55% over dose.